A photoactivable amino acid based on a novel functional coumarin-6-yl-alanine - Fonseca, Andrea Susana Cabral da (2012)
A novel fluorescent amino acid, L-4 chloromethylcoumarin-6-yl-alanine, was obtained from tyrosine by a Pechmann reaction. The assembly of the heterocyclic ring at the tyrosine side chain could be achieved before or after incorporation of tyrosine into a dipeptide, and amino acid and dipeptide ester conjugates were obtained by coupling to a model N-protected alanine. The behaviour of one of the fluorescent conjugates towards irradiation was studied in a photochemical reactor at different wavelengths (254, 300, 350 and 419 nm). The photoreaction course in methanol/HEPES buffer solution (80:20) was followed by HPLC/UV monitoring. It was found that the novel unnatural amino acid could act as a fluorescent label, due to its fluorescence properties, and, more importantly, as a photoactivable unit, due to the short irradiation times necessary to cleave the ester bond between the model amino acid and the coumarin-6-yl-alanine.